2010
DOI: 10.1007/s10762-010-9700-6
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Optimized Resonant Cavity for a Compact Sub-Terahertz Gyrotron

Abstract: Coherent sources of radiation in the sub-terahertz and the terahertz frequency range are in great demand for various spectroscopic studies (e.g. electron spin resonance spectroscopy, DNP/NMR spectroscopy etc.). The required levels of the output power as well as the needed specific spectral characteristics make the gyrotrons the most promising and high-performance devices for such applications. Recently, an initial design of a versatile second harmonic gyrotron utilizing a compact cryo-free 8 T superconducting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Various techniques for frequency control (continuous tunability; step-tunability; frequency modulation) that are being implemented in the innovative designs are discussed in [84,85]. A promising opportunity for widening of the tunability band, which is based on the use of up-tapered resonators has been explored recently [42,86].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various techniques for frequency control (continuous tunability; step-tunability; frequency modulation) that are being implemented in the innovative designs are discussed in [84,85]. A promising opportunity for widening of the tunability band, which is based on the use of up-tapered resonators has been explored recently [42,86].…”
Section: Discussionmentioning
confidence: 99%
“…Bulky and heavy devices like conventional gyrotrons are not suitable for such systems. This motivated us to develop a concept of a compact gyrotron [41,42], which is based on the utilization of compact liquid He-free superconducting magnets and slim tubes with a special design allowing its insertion in the relatively small diameter bore of the solenoid. The mentioned special design envisages also development of an optimized low-voltage and low-current MIG with reduced (minimized) radial dimensions.…”
Section: Recently Developed Gyrotrons Members Of the Fu Cw C And Fu mentioning
confidence: 99%
“…In this section we consider an inhomogeneous Helmholtz equation (25) where the right−hand term ) , ( z E ω represents the excitation of the cavity. It is supplemented with the same boundary conditions as in Sec.2.…”
Section: Solution Of the Boundary Value Problem For The Inhomogeneous...mentioning
confidence: 99%
“…This concept has been explored and applied to the CAD of several gyrotrons for spectroscopic applications [22,24]. Additionally, in [25] it has been demonstrated that a promising opportunity for widening of the tunability band is the usage of resonators in which the regular part of the cavity is replaced by a slightly up−tapered section [26]. It should be mentioned also that in most of the cases, the interaction which takes place in the cavity is the one between the electron beam and the backward−wave components of the HOAM (TE m,n,-q ), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We propose to use an uptapered cavity which is known to have several benefits [7,8]. The middle section of this cavity is twice as long (L 0 2 ¼ 30mm) as of the existing cavity (L 2 = 15 mm).…”
Section: Uptapered Cavitymentioning
confidence: 99%